2009
DOI: 10.1111/j.1439-0329.2009.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Phytophthora species in white oak (Quercus alba) decline in southern Ohio

Abstract: This study was initiated to investigate the possible role of Phytophthora species in white oak decline (Quercus alba) in southern Ohio at Scioto Trail State Forest. Surveys demonstrated the presence of four species of Phytophthora including one novel species. By far, the most common species was P. cinnamomi; P. citricola and P. cambivora were isolated infrequently. In few instances, P. cinnamomi was isolated from fine roots and necroses on larger roots. No special pattern of incidence was found, but P. cinnamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 44 publications
(136 reference statements)
2
24
1
Order By: Relevance
“…Surveys in temperate forests in other parts of the world support these findings, although they usually cover larger, more diverse forested areas and investigate only forest soils or streams [15][16][17][18][19][20][21][22][23][24][25][26]. Similar numbers of species and many of the same taxa are reported from soils, streams, or trees in the eastern USA and from Europe.…”
supporting
confidence: 63%
“…Surveys in temperate forests in other parts of the world support these findings, although they usually cover larger, more diverse forested areas and investigate only forest soils or streams [15][16][17][18][19][20][21][22][23][24][25][26]. Similar numbers of species and many of the same taxa are reported from soils, streams, or trees in the eastern USA and from Europe.…”
supporting
confidence: 63%
“…The event has not be described as a decline, defined by a slow gradual mortality, but rather a distinct abrupt mortality event that targets dominant long-lived species. Similar mortality events of this species have been observed and studied in Ohio by Balci et al (2010), who showed Pc associated with the same host tree species as in Missouri Ozarks (Q. alba).…”
Section: Soil Moisture and Forest Pathogenssupporting
confidence: 54%
“…Increasing climate variance, including excessive soil moisture either followed or preceded by drought contributes to the deleterious effect and the further advancement of this group of pathogens (DesprezLoustau et al, 2006). Balci et al (2010) directly implicated P. cinnamomi in white oak decline in Ohio and the presence of the root pathogen was associated with soils of higher moisture content. Experimentally, Corcobado et al (2014) simulated extreme weather events in seedlings and showed that drought may predispose seedlings to sensitivity to Phytopthora root infection.…”
Section: Soil Moisture and Forest Pathogensmentioning
confidence: 98%
“…Phytophthora cinnamomi, P. quercina (an oak-specific species), and several other Phytophthora spp. have been detected in recent decades in Europe (Jung et al, 1999(Jung et al, , 2002Gallego et al, 1999;Vettraino et al, 2002;Balci and Halmschlager, 2003) and in North America (Table 1; Balci et al, 2007Balci et al, , 2010Nagle et al, 2010). Although their role is not yet completely understood, it may be exacerbated by changing climate conditions (reviewed by Brasier, 1996;Jönsson, 2006).…”
Section: Emergent Biotic Agents Involved In Oak Decline: Pathogensmentioning
confidence: 96%